Unbearable life : a henealogy of political erasure - Bradley, Arthur (Insurrections., 2019)
Arthur Bradley explores the power to render life unlived from ancient Rome through the War on Terror. He argues that sovereignty is the power to decide what counts as being alive and what does not: to make life "unbearable," unrecognized as having lived or died.